TRANSFORMATION OF PUBLIC FINANCES: GENDER BUDGET - Taukesheva T.D.; Daudova G.V. (Pressing Problems of Public Administration, 2018)
The issue of gender budgeting in the context of reforming public  nances is elucidated. The results of gender analysis of programs and problems hindering the integration of gender budgeting in the budget process are highlighted. The approaches to incorporating the gender component into the compilation of state and local budgets are proposed.